2009
DOI: 10.1103/physrevlett.102.177003
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of the Electronic Structure of Tetragonalα-FeTe andα-FeSe Crystals: Evidence for a Bicollinear Antiferromagnetic Order

Abstract: By the first-principles electronic structure calculations, we find that the ground state of PbO-type tetragonal alpha-FeTe is in a bicollinear antiferromagnetic order, in which the Fe local moments (approximately 2.5 microB) align ferromagnetically along a diagonal direction and antiferromagnetically along the other diagonal direction on the Fe square lattice. This novel bicollinear order results from the interplay among the nearest, the next-nearest, and the next-next-nearest neighbor superexchange interactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
308
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(339 citation statements)
references
References 19 publications
29
308
1
1
Order By: Relevance
“…This series of transitions occurs in the same regime where the initial magnetic order at high temperature is an incommensurate spin density wave, that transforms abruptly to a nearlycommensurate version of the bicollinear structure. 25,26 The bicollinear magnetic structure can be obtained from DFT calculations 35,42,43 ; however, interpretation of the components determining the magnetic structure are usually done in terms of simpler model Hamiltonians. 36,37,44 It is clear that because of competing interactions, the bicollinear and collinear antiferromagnetic states 4 are close in energy.…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…This series of transitions occurs in the same regime where the initial magnetic order at high temperature is an incommensurate spin density wave, that transforms abruptly to a nearlycommensurate version of the bicollinear structure. 25,26 The bicollinear magnetic structure can be obtained from DFT calculations 35,42,43 ; however, interpretation of the components determining the magnetic structure are usually done in terms of simpler model Hamiltonians. 36,37,44 It is clear that because of competing interactions, the bicollinear and collinear antiferromagnetic states 4 are close in energy.…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
“…11,31,34 Later first-principles calculations have identified the role of local moments and the importance of Hund's exchange coupling, and have provided a more convincing description of the experimental observations. [35][36][37][38] A recent study on Fe 1.1 Te has shown that the localized electrons that contribute to magnetism are not isolated from the itinerant ones, but instead are entangled, as indicated by a temperature-induced enhancement of the instantaneous magnetic moment. 20 In this paper, we use Cu to replace Fe in Fe 1.1 Te, aiming to study the impact of the weakly magnetic Cu dopants on the magnetic order, which we characterize with neutron scattering.…”
mentioning
confidence: 99%
“…The fact that the unconventional superconductivity in iron pnictides and chalcogenides is interplayed with magnetism motivated extensive research on the origin of antiferromagnetism of iron pnictide and chalcogenide superconductor parent compounds [1][2][3][4][5][6][7][8][9][10] . Iron pnictides parent compounds, such as LaOFeAs and BaFe 2 As 2 , exhibit "single-stripe" antiferromagnetic (AFM) order with the in-plane component of AFM wave vector along the Fermi surface (FS) nesting direction (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this mechanism cannot be used to interpret the antiferromagnetism in Fe 1+y Te since its in-plane component of the AFM wavevector is (π,0), rather than the FS nesting vector (π,π). In addition to the picture of FS-driven magnetism, various models based on local moment superexchange interactions have been proposed [24][25][26][27][28][29] and a scenario of local moments coupled to a low number of itinerant electrons is also considered 24,27,[30][31] 18 . This result is in a good agreement with the theoretical result stated above.…”
Section: Introductionmentioning
confidence: 99%